Thermoelastic Behavior of a Hollow Cylinder Using Space-time Fractional Heat Conduction: A Quasi-static Approach - Warbhe, Shrikant; Gujarkar, Vishakha (Zielona Góra: Uniwersytet Zielonogórski)
The present study examines thermoelastic behaviour of a hollow cylinder governed by the space-time fractional heat conduction equation, employing a quasi-static approach. The analysis utilizes the Caputo time fractional derivative and finite Riesz space fractional derivative. An arbitrary temperature is applied to the upper surface of the cylinder while, the other boundaries are maintained at zero temperature. The heat conduction equation is solved using the integral transform technique. A mathematical model is developed specifically for pure copper material. The effects of varying the fractional orders of space and time on thermoelasticity, influenced by changes in thermal conductivity, are investigated and the results are depicted graphically.
Keywords: integral transform; Mittag-Leffler function; quasi-static; fractional derivatives and integrals; thermal stresses